2013
DOI: 10.1038/mp.2013.19
|View full text |Cite
|
Sign up to set email alerts
|

APOE and BCHE as modulators of cerebral amyloid deposition: a florbetapir PET genome-wide association study

Abstract: Deposition of amyloid-β (Aβ) in the cerebral cortex is thought to be a pivotal event in Alzheimer’s disease (AD) pathogenesis with a significant genetic contribution. Molecular imaging can provide an early noninvasive phenotype but small samples have prohibited genome-wide association studies (GWAS) of cortical Aβ load until now. We employed florbetapir (18F) positron emission tomography (PET) imaging to assess brain Aβ levels in vivo for 555 participants from the Alzheimer’s Disease Neuroimaging Initiative (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
147
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(165 citation statements)
references
References 45 publications
13
147
2
1
Order By: Relevance
“…Stein et al [50] conducted the first voxel-wise GWAS and suggested CSMD2 and CADPS2 as candidate genes for future investigation. Ramanan et al [51] used florbetapir ( 18 F) positron emission tomography (PET) to evaluate the cortical load of amyloid b, which revealed an association of APOE and BCHE with this load. Carrasquillo et al [52] revealed the association of IDE with amyloid b40 and total amyloid b levels in plasma.…”
Section: Ad Biomarkers From Neuroimaging and In Fluids As The Phenotypementioning
confidence: 99%
“…Stein et al [50] conducted the first voxel-wise GWAS and suggested CSMD2 and CADPS2 as candidate genes for future investigation. Ramanan et al [51] used florbetapir ( 18 F) positron emission tomography (PET) to evaluate the cortical load of amyloid b, which revealed an association of APOE and BCHE with this load. Carrasquillo et al [52] revealed the association of IDE with amyloid b40 and total amyloid b levels in plasma.…”
Section: Ad Biomarkers From Neuroimaging and In Fluids As The Phenotypementioning
confidence: 99%
“…Rs2075650 within APOE/TOMM40 has been studied for its associations with several age-related disorders and diseases in GWAS, such as cognitive decline 27,28 and Alzheimer's disease (AD), [29][30][31] as well as AMD. 12,13 Apolipoprotein E (ApoE), encoded by the APOE gene, was recognized for its crucial role in lipoprotein transport.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of APOE also facilitates the molecular interaction between amyloid beta and Butyrylcholineesterase (BCHE) gene which results in the formation of a complex BCHE-Abeta-APOE (BaβA) complex [165][166][167]. This complex alters the structure of BCHE which accelerates the catalytic activity of the enzyme.…”
Section: Hypothetical Mechanism For Cerebral Blood Flow In Admentioning
confidence: 99%